A Bone Conduction Implantable Device as a Functional Treatment Option in Unilateral Microtia with Bilateral Stapes Ankylosis: A Report of Two Cases - Zanetti, Diego (Am J Case Rep, 2018)
Case series Patient: Female, 29 • Male, 35 Final Diagnosis: Microtia with stapedial ankylosis Symptoms: Hearing loss Medication: — Clinical Procedure: Bone conduction implantable device Specialty: Audiology OBJECTIVE: Congenital defects/diseases BACKGROUND: Implantable devices have been proposed as an alternative to hearing aids and auditory canal reconstruction in patients with microtia (congenital aural atresia), which includes a malformation of the external and middle ear. This report is of two rare cases of microtia associated with congenital stapes ankylosis treated with an implantable device and describes the treatment outcomes. CASE REPORT: Two siblings from Ecuador, a 29-year-old woman, and her 35-year-old brother, were born with unilateral type II microtia with bilateral external auditory canal atresia and conductive hearing loss. Pre-operatively, high-resolution computed tomography (HRCT) imaging was performed using FastView software to allow placement of a bone conduction-floating mass transducer (BC-FMT) to couple a Bonebridge bone conduction implant (BCI) system in both patients. Pure-tone audiometry (PTA) testing and speech audiology were performed. The Abbreviated Profile of Hearing Aid Benefit (APHAB) and the Speech, Spatial and Qualities (SSQ) of hearing scale questionnaires and scoring systems were used. Following activation of the implantable device, both patients achieved improved bilateral conductive hearing with sound-field (field-free) thresholds >25 dB, and speech recognition scores >90%. In both cases, hearing improvement remained at three years following surgery. CONCLUSIONS: To our knowledge, these are the first reported cases of microtia with congenital stapes ankylosis successfully treated with a bone conduction implantable device. Patients with microtia and stapes ankylosis who are reluctant to undergo surgery may benefit from unilateral or bilateral, short-term or long-term use of a Bonebridge bone conduction implantable device.